The influence of training and expertise on the multisensory perception of beer: A review - Van Doorn, G; Watson, S; Timora, J; Spence, C (Elsevier, 2019)
This review critically evaluates the literature documenting the impact of training on people’s perception of beer. In certain circumstances, training has been shown to improve people’s ability to match and identify beers, and to discriminate between beers and between the distinctive attributes of beer. However, a reasonably consistent finding is that the benefits of beer training do not seem to generalise to novel beers (i.e., those not experienced during training). As such, training would appear to improve the capacity to label perception and/or people’s recognition memory for beers, rather than necessarily influencing perception itself. Given how much beer is consumed annually, it is surprising that there has not been more published research into the role that training plays in this particular beverage category. Part of the reason for this may relate to (a) the limited role of experts in this field (e.g., primarily restricted to product testing and quality control; as compared to their much more prominent role in the world of wine), (b) the fact that training is an expensive and time-consuming process, and (c) it is wrongly assumed that the effects of training are similar across different beverage categories (e.g., beer and wine). We suggest that further efforts are therefore required before it will be possible to confidently conclude that training lowers the perceptual thresholds, and enhances the perceptual discrimination abilities, of beer experts above those of novices.